High Order in a Self‐Assembled Iridium(III) Complex Gelator Towards Nanostructured IrO2 Thin Films. Issue 20 (25th September 2017) - Scarpelli, Francesca; Ionescu, Andreea; Aiello, Iolinda; La Deda, Massimo; Crispini, Alessandra; Ghedini, Mauro; Brunelli, Elvira; Sesti, Settimio; Godbert, Nicolas
Abstract: The preparation and characterization of a new metallogelator based on the Ir III discrete cyclometalated complex [(ppy)2 Ir(bpy)](CH3 CH2 OCH2 CO2 ) are reported, where H(ppy) is 2‐phenylpiridine and bpy is 2, 2′‐bipyridine, which is used as an ancillary ligand. The compound is able to self‐assemble in water in a range of concentrations between 3 % and 6 % w/w, creating a luminescent ordered supramolecular gel. The gel and xerogel architectures were investigated through polarized optical microscopy (POM), SEM and TEM microscopies coupled with powder X‐ray diffraction. The gel supramolecular organization is characterized by columnar tetragonal strands, already present at high dilution conditions, of cations surrounded by counteranions. These strands, in turn, are self‐assembled in an oblique columnar cell upon gelification. The xerogel thin films obtained upon complete dehydration maintained the gel supramolecular order and can be used as a precursor for the preparation of nanostructured IrO2 thin films. Abstract : Self‐assembling metallogels : Nanostructured thin films of iridium oxide have been prepared from highly organized self‐assembled water‐soluble Ir III metallogels. The supramolecular architecture of the gel has been elucidated. The xerogels obtained from the total dehydration of the gel phase maintained their arrangement and upon calcination nanostructured IrO2 thin films were obtained.